Rich or Poor: Experimental Evidence on the Self-Validation Hypothesis and Tax Compliance Behavior - Nur Anita; Hutomo Atman Maulana; Frida Fanani Rohma (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
This study aims to investigate the influence of the self-validation hypothesis on tax compliance, considering whether individual income is high or low. This research uses an experimental method with a 22 factorial design. The participants in the experiment were students of public financial accounting at the Politeknik Negeri Bengkalis. Through the Elaboration Likelihood Model (ELM) theory, this research helps explain why tax messages have different impacts on various groups of people. Interestingly, the research findings indicate that individuals with high incomes are more likely to comply with taxes compared to those with low incomes. To improve tax compliance, the government must design communication strategies tailored to taxpayers' levels of motivation and cognitive capacity.